Assessment of serological markers of genital chlamydia trachomatis infection among the gynaecology patients attending Babcock University teaching hospital, Ilishan-Remo, Ogun state, Nigeria. (2019)
Genital Chlamydia trachomatis infection causes significant morbidity and mortality in women. A number of epidemiologic studies have suggested that Polymerase Chain Reaction (PCR) is more accurate as a diagnostic tool for Chlamydia trachomatis.However, the use of serological markers may be cost effective and practical in diagnosing and estimating the burden of the disease in resource limited countries.This study was aimed at determining the serological markers (IgG, IgM and IgA) of Chlamydia trachomatis, evaluate the association between Chlamydia trachomatis infection and the sociodemographic characteristics and clinical diagnosis of the participants. This was a cross sectional hospital-based study in which blood samples from 145 consenting participants were tested for IgG, IgM and IgA antibodies against Chlamydia trachomatis using enzyme linked immunosorbent assay and their clinical diagnosis, retrieved from their case notes. The cumulative prevalence of seropositivity for Chlamydia trachomatis (IgG, IgM, IgA) was 112 (77.2%) while 33 (22.8%) were seronegative. The overall predominant seromarker was IgG 91(62.8%) while IgM and IgA accounted for 85(58.6%) and 54(37.2%) respectively. A statistically significant association was found between Chlamydia trachomatis infection and PID (p value = 0.031), primary infertility (p value 0.011) and level of income (p value= (0,045).